2017
DOI: 10.1016/j.jlumin.2017.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Coupling between surface plasmon resonance and Sm3+ ions induced enhancement of luminescence properties in fluoro-tellurite glasses

Abstract: Fluoro-tellurite glasses co-activated with Samarium (Sm 3+) ions and silver nanoparticles (Ag NPs) were prepared using melt quenching technique. The nucleation and growth of Ag NPs were controlled by thermal annealing process. X-ray diffraction (XRD), transmission electron microscopy (TEM), differential scanning calorimetry (DSC), UV-vis-NIR absorption spectroscopy, photoluminescence (PL) and PL lifetime spectroscopy were used to examine the annealing time dependence of the structural and luminescent propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…A similar shift in the band gap due to the addition of Ag 2 O was also reported in [30]. The presence of silver nanoparticles is known to lead to an absorption band at ~400 nm, due to the surface plasmon resonance (SPR) of Ag NPs [2,7]. As shown in Figure 2a, no absorption band at ~400 nm can be seen indicating that Ag are dispersed in the network in a small size of Ag species.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…A similar shift in the band gap due to the addition of Ag 2 O was also reported in [30]. The presence of silver nanoparticles is known to lead to an absorption band at ~400 nm, due to the surface plasmon resonance (SPR) of Ag NPs [2,7]. As shown in Figure 2a, no absorption band at ~400 nm can be seen indicating that Ag are dispersed in the network in a small size of Ag species.…”
Section: Resultssupporting
confidence: 75%
“…Recently, particular interest has been paid to glasses containing Ag nanoparticles (NPs) due to the spectacular improvement of luminescence properties, which benefit photonic applications [6,7]. In fact, collective charge density oscillations at the Ag NP surface, known as surface plasmon resonance (SPR), offers an opportunity to improve the photoluminescence (PL) properties of RE in glasses.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of the published research only provided TEM images of the Au/Ag doped tellurite glasses showing the formation of crystalline NPs [17][18][19] , with no further evidence con rming the elemental nature of the observed crystalline NPs. In addition, distinct LSPR features in tellurite glasses have been demonstrated in only a few reports 20,21 . The ability to tune the location and intensity of the LSPR band remains a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Among the rare-earth ions, Sm 3+ has a 4f 5 electron configuration and shows strong PL in the orange-red ( 580-660 nm) and near-infrared regions (~0.95-1.32 μm) under excitation at  = 400 nm, which makes Sm 3+ -doped glasses good candidates for solar spectral converters [20,21]. Several researchers have focused on the PL enhancement owing to Sm 3+ via SPR in various glass matrixes, such as tellurite-based glass [22][23][24][25], phosphate-based glass [26,27], lead-based glass [28], oxyfluoride glass [29], antimony glass [30], chloroborosilicate glass [31], and ion-exchanged alkali containing glass [32,33]. Feras et al enhanced the PL intensity of Sm 3+ up to seven times in tellurite glass [22].…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have focused on the PL enhancement owing to Sm 3+ via SPR in various glass matrixes, such as tellurite-based glass [22][23][24][25], phosphate-based glass [26,27], lead-based glass [28], oxyfluoride glass [29], antimony glass [30], chloroborosilicate glass [31], and ion-exchanged alkali containing glass [32,33]. Feras et al enhanced the PL intensity of Sm 3+ up to seven times in tellurite glass [22]. Karmakar et al reported that, in chloroborosilicate glass doped with Ag nanoparticles, the PL of Sm 3+ at = 600-650 nm was slightly enhanced by up to 4% [31].…”
Section: Introductionmentioning
confidence: 99%